PENGEMBANGAN MEDIA DAILY PLAY SUITCASE TERHADAP PERILAKU MORAL DAN AGAMA ANAK USIA 5-6 TAHUN - Dian Diovriska; Zulkifli N Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Early childhood is a child who is in the stage of concrete precoposional development as suggested by Piaget. Meanwhile, moral value is an abstract concept, so in this case the child cannot immediately accept what the teacher or parent teaches, which is abstract in nature, moral and religious behavior is abstract for the child, for that the teacher must be able to teach moral and religious behavior. . in an interesting and creative way. According to Guslinda and Rita Kurnia (2018), the use of instructional media in the teaching and learning process has a big influence and has an impact on children's interests and motivation. In order for teachers to successfully instill moral values in early childhood, they are required to be creative in determining learning media. Media Daily Play Suitcase is a medium used to convey information or messages related to moral and religious learning in its activities using a modified suitcase according to the moral and religious learning needs of early childhood. The purpose of this research is to develop and determine the feasibility of the Media Daily Play Suitcase in improving the moral and religious behavior of children aged 5-6 years. This research is expected to be used as a material consideration for teachers in choosing effective learning media for religious moral behavior in children related to the influence of the Media Daily Play Suitcase for Children's Religious Moral Behavior. This research uses procedural methods according to Borg and Gall, namely research and development of R & D (Research and Development). Validation was carried out by material and media experts as well as 6 teachers from TK N Pembina 3 Pekanbaru. The results showed that the average evaluation of the material and media expert validators got a percentage of> 80% so that the assessment achieved by the material and media expert validators got the "Eligible" category. Meanwhile, the average assessment result of 6 certification teachers received a percentage of 100% in the "Very Appropriate" category. So it can be concluded that the daily play suitcase media is very valid, very effective, and very suitable for use as a medium for learning morals and religion for early childhood.Key Words: Daily Play Suitcase, Moral and Religious.